Pengembangan Bahan Ajar IPA Berbentuk Komik Pada Materi Sistem Ekskresi Untuk SMP/MT’s Kelas VIII - Mutiara Iga Nuraeni; Mohammad Wildan Habibi (Universitas Islam Negeri Maulana Malik Ibrahim Malang)
Research and development of science teaching materials in the form of comics on the excretion system material is based on the lack of reading interest of class VIII students of SMPN 1 Kedungjajang regarding the Excretion System and the limited learning resources that can facilitate students' understanding. This study aims to determine the validity and response of students to science teaching materials in the form of comic class VIII on the excretion system material in SMP. The type of research used is Research and Development. By using the 4-D development model, it includes define, design, develop and disseminate. However, the research is only limited to the develop stage. The ujit subjects in this study were material experts, media experts, science teachers and students. The instrument used by researchers was a questionnaire. The research data were analyzed using descriptive analysis. The results of the validity of science teaching materials in the form of comics are in the very feasible category after going through the validation process of experts with validation of material experts at 92%, media experts at 90%, and science teachers at 93%. While the assessment for the response of students was 87.40%. Based on the research developed, science teaching materials in the form of comics are stated to be very valid and can be used in classroom learning.